Identification of recruited myeloid cells important for the development of hepatic metastasis - Gordon-Weeks, A (2015)
Hepatic metastases are a frequent cause of mortality in colon cancer patients. Many patients with hepatic metastasis have large tumour burden, signaling the need for therapies capable of down-staging metastatic disease. Research evidence indicates that immune cells promote the metastasis of various primary cancers. We wish to determine whether immune cells play a role in the promotion of hepatic colon cancer metastasis. Using the well-characterised method of intrasplenic tumour cell injection, we developed hepatic metastases in both immunocompetent and immunoincompetent mice using a range of murine and human cancer cell lines. We analysed the immune cell infiltrates associated with hepatic metastases using flow cytometry and identified chemokines responsible for their recruitment using targeted protein arrays. The effect of immune cell depletion or inhibition of immune cell recruitment was determined using various in-vivo imaging techniques. Hepatic metastases developed using the murine colon cancer cell line MC38 were associated with CD11b+/Gr1mid/CCR2+ monocytes, the recruitment of which was delayed by inhibition of tumour-derived CCL2. In contrast, human HT29, HCT-116 and LoVo hepatic metastases in SCID mice were associated with infiltrates of CD45+/CXCR2+ neutrophils recruited in response to tumour-derived Macrophage Inhibitory Factor (MIF). Depletion of Gr1mid cells in CD11b-DTR transgenic mice delayed MC38 metastasis development, whilst neutrophil depletion using anti-Ly6G antibodies significantly inhibited the growth of HT29, HCT-116 and LoVo hepatic metastases. The neutrophils recruited to HT29, HCT-116 and LoVo hepatic metastases promoted angiogenesis, potentially through the expression of fibtroblast growth factor-2. This work demonstrates a role for myeloid cells in the development of hepatic metastasis from colon cancer and in doing so identifies various potential therapeutic targets.